Integration of Islamic Religious Education Values in the Adiwiyata Program as an Effort to Develop Students' Environmental Piety - Nopi Risdiani; Wawan Hermawan; Agus Fakhruddin (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
The global environmental crisis demands an educational approach that is not only ecological but also based on spiritual values. This study aims to explore the strategies and challenges in the integration of Islamic Religious Education (PAI) values into the Adiwiyata Program as an effort to form students' environmental piety at the elementary school level. This research used a qualitative approach with a case study method, data were collected through observation, interviews, and documentation studies, then analyzed thematically using the Miles and Huberman interactive model. The results showed that Islamic values such as khalifah, rahmatan lil 'alamin, gratitude, and thaharah were successfully internalized through integrative strategies in the curriculum, habituation, exemplary teachers, student regeneration, and collaboration with parents and the community. The obstacles faced include regeneration of cadres and limited understanding of students, which are overcome through intensive coaching and layered evaluation. This study concludes that the integration of PAI values in the Adiwiyata Program effectively shapes environmental piety and can be an applicable model of ecological character education based on Islamic spirituality.